The heavens : a novel - Newman, Sandra, 1965- (Grove Press, 2019)
"A young man, Ben, meets a young woman, Kate--and they begin to fall in love. From their first meeting, Ben knows Kate is unworldly and fanciful, so at first he isn't that concerned when she tells him about the recurring dream she's had since childhood. In the dream, she's transported to the past, where she lives a second life as Emilia, the mistress of a nobleman in Elizabethan England. But for Kate, the dream becomes increasingly real and compelling until it threatens to overwhelm her life."--